1992
DOI: 10.1142/s0192415x92000369
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and the Nervous System

Abstract: Acupuncture is based on neuroanatomy and neurophysiology. At each acupuncture point, there are peripheral nerves and terminals. Acupuncture will be useful for further understanding of the nervous system. A conceptual view of acupuncture's physiology is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…Cai 17 has reported the correlation of acupuncture and the nervous system. He pointed out that there are peripheral nerves and terminals at each acupuncture point.…”
Section: Discussionmentioning
confidence: 99%
“…Cai 17 has reported the correlation of acupuncture and the nervous system. He pointed out that there are peripheral nerves and terminals at each acupuncture point.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our results showed that acupuncture increased skin temperature, suggesting that the increases of skin temperature resulted from cutaneous vasodilation due to acupunctureinduced parasympathetic stress response. This suggestion is supported by previous studies showing that central command is generated by a potent stimulus and plays an important role in cutaneous parasympathetic vasodilation.…”
Section: Blood Flow Effect Of Acupuncturementioning
confidence: 53%
“…Acupuncture stimulates peripheral sensory nerves and their endings, increases cutaneous blood flow and microcirculation, and releases neurotransmitter, neuropeptides and hormones. 23 Kashiba and Ueda reported 24 that acupuncture to the skin induces release of substance P and calcitonin gene-related peptide from peripheral terminals of primary sensory neurons in a rat model. Jansen reported that electroacupuncture in a rat increases cutaneous blood flow, similar to the effect seen with SP and calcitonin gene-related peptide injection into the central vein.…”
Section: Discussionmentioning
confidence: 99%
“…By using electric impedance, Lin showed that muscle layers were the major site of de-qi in the 22 acupoints in the back [128]. The role of the nervous system in de-qi has also been well described, and some researches in this review shared their opinions as well [24,129]. The relevant nerves can be found in certain region surrounding the acupuncture point, and it is likely that nerves are provoked during needle manipulation.…”
Section: Discussionmentioning
confidence: 90%